Welcome to mathimatikoi.org forum; Enjoy your visit here.

## A series involving Harmonic numbers

Calculus (Integrals, Series)
mathofusva
Articles: 0
Posts: 33
Joined: Tue May 10, 2016 3:56 pm

### A series involving Harmonic numbers

Show that
$$\sum_{n=1}^\infty\,\frac{(-1)^{n+1}}{(n+1)^2}H_nH_{n+1} = \frac{\pi^4}{480},$$
where $H_n$ is the $n$-th Harmonic number.
Tolaso J Kos
Articles: 2
Posts: 855
Joined: Sat Nov 07, 2015 6:12 pm
Location: Larisa
Contact:

### Re: A series involving Harmonic numbers

Let $\mathcal{H}_n$ denote the $n$-th harmonic number and consider the power series

$$\sum_{n=1}^{\infty} \mathcal{H}_n \mathcal{H}_{n+1} x^n \quad , \quad -1 \leq x <1$$

Since $\mathcal{H}_{n+1} = \mathcal{H}_n + \frac{1}{n+1}$ then we have that

\begin{align*}
\sum_{n=1}^{\infty} \mathcal{H}_n \mathcal{H}_{n+1} x^n &= \sum_{n=1}^{\infty} \mathcal{H}_n \left ( \mathcal{H}_n + \frac{1}{n+1} \right ) x^n \\
&=\sum_{n=1}^{\infty} \mathcal{H}_n^2 x^n + \sum_{n=1}^{\infty} \frac{\mathcal{H}_n}{n+1}x^n \\
&=\frac{\log^2 (1-x) +{\rm Li}_2(x)}{1-x} + \frac{\log^2(1-x)}{2x}
\end{align*}

Thus mapping $x \mapsto -x$ we get that

$$\sum_{n=1}^{\infty} (-1)^{n+1} \mathcal{H}_n \mathcal{H}_{n+1} x^n = - \frac{\log^2 (1+x)+{\rm Li}_2(-x)}{1+x} + \frac{\log^2(1+x)}{2x}$$

Integrating we get that

\begin{align*}
\int \sum_{n=1}^{\infty} (-1)^{n+1} \mathcal{H}_n \mathcal{H}_{n+1} x^n \, {\rm d}x&= \sum_{n=1}^{\infty} (-1)^{n+1} \mathcal{H}_n \mathcal{H}_{n+1} \int x^n \, {\rm d}x \\
&= \sum_{n=1}^{\infty} \frac{(-1)^{n-1} \mathcal{H}_n \mathcal{H}_{n+1} x^{n+1}}{n+1}\\
&=\int \left ( \frac{\log^2 (1+x)+{\rm Li}_2(-x)}{1+x} + \frac{\log^2(1+x)}{2x} \right ) \, {\rm d}x\\
&= -3 {\rm Li}_3 (1+x) + {\rm Li}_2(-x) \log(1+x)+ 3{\rm Li}_2 (1+x) \log(1+x) \\
&\quad \quad + \frac{\log^3(1+x)}{3} + \frac{3}{2} \log(-x) \log^2 \left ( 1+x \right )
\end{align*}

Hence

$$\sum_{n=1}^{\infty} \frac{(-1)^{n-1} \mathcal{H}_n \mathcal{H}_{n+1} x^{n-1}}{n+1} = \frac{1}{x} \bigg[-3 {\rm Li}_3 (1+x) + {\rm Li}_2(-x) \log(1+x)+$$
$$+3{\rm Li}_2 (1+x) \log(1+x)+ \frac{\log^3(1+x)}{3} + \frac{3}{2} \log(-x) \log^2 \left ( 1+x \right ) \bigg]$$

Integrating from $0$ to $1$ we must get the result .... There must be something more sufficient and clever here , no?
Imagination is much more important than knowledge.
r9m
Articles: 0
Posts: 59
Joined: Thu Dec 10, 2015 1:58 pm
Location: India
Contact:

### Re: A series involving Harmonic numbers

This is closely related to problem 11993 from American Mathematical Monthly Journal.

Now the problem presented in that integral form can be dealt with rather easily and one avoids having to calculate the last Euler Sum I left off .. There's an old blog post of mine with spoilers for this problem, but honestly the problem is much simpler than I ever imagined.